Quality control of herbal medicines in hyperlipidaemia: metabolomics approach - Abu Bakar Sajak, Azliana; Azlan, Azrina; Abas, Faridah; Hamzah, Hazilawati (Universiti Putra Malaysia, 2023)
Hyperlipidaemia is one of the essential public health risk factors that can cause other metabolic diseases such as cardiovascular diseases and diabetes. Dieting and healthy lifestyle have been among the primary approaches. However, medication is required to regulate the lipid profile in some instances. Therefore, there has been an increase in interest in using or integrating herbal medicine with modern medicine in treating hyperlipidaemia. Nonetheless, preparing standardised herbal extract or products has been one of the major challenges in the herbal industry. Standardising herbal extract or product (single plant-based or mixture of multiple herbs) is needed to ensure the quality, safety, and efficacy of the herbal maintained from batch to batch before it is released to the market. The present review thus evaluates several herbal plants with anti-hyperlipidaemic activities, quality control using chemical markers, and metabolomics application in herbal plants.